Psychophysical health status of breast cancer survivors and effects of 12 weeks of aerobic training. (May 2017) - Di Blasio, Andrea; Morano, Teresa; Cianchetti, Ettore; Gallina, Sabina; Bucci, Ines; Di Santo, Serena; Tinari, Camilla; Di Donato, Francesco; Izzicupo, Pascal; Di Baldassarre, Angela; Cimini, Alessandra; Napolitano, Giorgio
Abstract: The aim of this study was to analyse the health status of breast cancer survivors and the effects of 12 weeks of aerobic training. Twenty-three breast cancer survivors (51.71 ± 3.17 years) and 23 healthy women (50.73 ± 2.97 years) were investigated for body composition, daily physical activity, quality of life, salivary cortisol, and DHEA-S. Breast cancer survivors were then aerobically trained for 12 weeks. Breast cancer survivors have a worse psychophysical health than healthy women. Aerobic training increased salivary DHEA-S, aerobic fitness, self-reported health, and nocturnal sleeping time and reduced salivary cortisol in breast cancer survivors. Salivary cortisol variation correlated with change of sleeping time and self-reported health. Salivary DHEA-S correlated with change of self-reported physical pain and general health as well. Breast cancer survivors can live in a situation of continuous distress, requiring a multidisciplinary approach. Twelve weeks of aerobic training improve the psychophysical health of breast cancer survivors.